TRNP1 regulates tumorigenesis and enhances immunotherapy response via c-Kit/STAT3 signaling in hepatocellular carcinoma - Hu, Jian; Zhang, Ning; Ma, Yanfen; Zhou, Nian; Wang, Xiaoqian; Zhang, Kaige; Wu, Qian; Wang, Xiaoqin; Mao, Feifei (Journal of Gastrointestinal Oncology, 2026)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related deaths worldwide, with a poor prognosis and high mortality rates. Therapeutic resistance, high recurrence, and limited treatment options contribute to its aggressive nature. The TMF1-regulated nuclear protein 1 (TRNP1) is a highly conserved nuclear protein, recently implicated in tumorigenesis. TRNP1 is upregulated in HCC, but its role in tumorigenesis and immunotherapy resistance remains underexplored. This study investigates the mechanical roles of TRNP1 in HCC progression through the c-Kit/signal transducers and activators of transcription 3 (STAT3) signaling pathway and its impact on immunotherapy efficacy, particularly in the context of programmed cell death protein 1 (PD-1) blockade.